Effect of pea stunt disease on shoot development field pea - R.N. SINGH, A.T. KHAN and (Indian Phytopathology, 2002)
Pea stunt disease, incited by red clover vein mosaic virus, caused 42.73, 50.96, 42.46 and 36.31% reduction, respectively, in shoot length, shoot volume, number of branches per plant and size of internodes in the moderately diseased plants. Reduction increased progressively with the increasing severity of the disease in case of size of internodes. In case of shoot length, shoot volume and nuber of branches, heavily diseased plants, instead of decrease registered significant increase over moderately diseased ones. The disease induced production of 72.98, 83.89 and 73.76% higher number of internodes, respectively, in the moderately diseased, heavily diseased and severely diseased plants over healthy ones.